Recombinant subunit vaccines protect guinea pigs from lethal Ebola virus challenge. Issue 47 (8th November 2019) - Lehrer, Axel T.; Wong, Teri-Ann S.; Lieberman, Michael M.; Johns, Lisa; Medina, Liana; Feldmann, Friederike; Feldmann, Heinz; Marzi, Andrea
Abstract: Ebola virus (EBOV) is among the deadliest pathogens known to man causing infrequent outbreaks of hemorrhagic disease. In humans, the case fatality rates in the outbreaks can reach 90%. During the West African epidemic almost 30, 000 people were infected and of these over 11, 000 fatalities were reported. Currently, we are facing an uncontained larger outbreak in the Democratic Republic of the Congo. Even though EBOV was discovered in 1976, extensive efforts to develop countermeasures, particularly therapeutics and vaccines, started late and there is still no FDA-approved product available. Nevertheless, one candidate vaccine, the rVSV-ZEBOV, is being used in clinical trials during the current outbreak with the hope of ending the human transmission chains. However, adverse reactions to administration of some EBOV vaccines have been reported; therefore, we have developed a safe and efficacious formulation of insect-cell derived adjuvanted protein vaccines. Vaccine candidates containing the EBOV glycoprotein with or without matrix proteins VP24 and VP40 formulated with one of three different adjuvants were tested in guinea pigs for immunogenicity and efficacy against lethal EBOV challenge. The results demonstrated that these vaccine candidates engendered high titers of antigen-specific antibodies in immunized animals and two of these vaccine candidates afforded complete or nearly complete protection against lethal challenge. Interestingly, we found a sex bias in partially protected immunized groups with male guinea pigs succumbing to disease and females surviving. In summary, we developed a safe and immunogenic adjuvanted subunit vaccine uniformly protective against EBOV disease in guinea pigs.